2017
DOI: 10.1155/2017/4921090
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Spherical Aberration and Corneal Asphericity after Small Incision Lenticule Extraction and Femtosecond Laser-Assisted LASIK

Abstract: Purpose To investigate corneal spherical aberration and corneal asphericity after small incision lenticule extraction (SMILE) and femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK). Methods This study enrolled 70 patients having SMILE and 64 subjects receiving FS-LASIK. The preoperative spherical equivalent (SE) was −5.83 ± 1.23 diopters (D) and −6.20 ± 1.52 D, respectively. The uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), SE, corneal spherical aberration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…The DA and AA accounted for the majority of the total aberrations, hence the TLOA and TWA also decreased after the operation. As to the higher order aberrations, the increasing trend was similar to the previous studies [ 12 , 38 , 39 ]. Due to the surgery incision and the postoperative wound healing, the asymmetry of eye plane such as irregularity, inclination and decentration might occur, which could be reflected by CAs [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…The DA and AA accounted for the majority of the total aberrations, hence the TLOA and TWA also decreased after the operation. As to the higher order aberrations, the increasing trend was similar to the previous studies [ 12 , 38 , 39 ]. Due to the surgery incision and the postoperative wound healing, the asymmetry of eye plane such as irregularity, inclination and decentration might occur, which could be reflected by CAs [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have found that the morphological changes of the anterior corneal surface after SMILE and FS-LASIK are different [ 9 ], and the introduction of HOAs into SMILE after surgery is lower than that into FS-LASIK. Zhang et al [ 10 ] showed that Trans-PRK changes the corneal curvature to a greater extent and the visual quality ( Q -value, aberrations) to a lesser extent than FS-LASIK.…”
Section: Introductionmentioning
confidence: 99%
“…However, postoperative increase in coma was smaller in SMILE than LASEK and was similar to that of femtosecond (FS)-LASIK [22,24]. Studies reported that early wound healing response of SMILE is less reactive than that of FS-LASIK [25] and that the corneal epithelial remodeling after SMILE exhib- ited lesser shift toward oblateness than that after FS-LASIK [24]. Such advantages may compensate for the effect of decentration of SMILE compared with that of FS-LASIK.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies have reported that single incisions in the SMILE procedure may cause an imbalanced corneal healing response and induce optical changes, which could increase coma postoperatively [23]. However, postoperative increase in coma was smaller in SMILE than LASEK and was similar to that of femtosecond (FS)-LASIK [22,24]. Studies reported that early wound healing response of SMILE is less reactive than that of FS-LASIK [25] and that the corneal epithelial remodeling after SMILE exhib- ited lesser shift toward oblateness than that after FS-LASIK [24].…”
Section: Discussionmentioning
confidence: 96%